Pengelolaan Jalan Nafas Sulit - Moulida Aziza; Abrar Abrar (Jurnal Anestesi, 2025)
Intubation failure occurs in 1 case out of 200-2000 cases under selective general anesthesia. A difficult airway is a clinical situation in which the anesthesiologist has difficulty in ventilation using a mask, tracheal intubation or both. A difficult airway is an interaction between patient factors, clinical conditions, and the practitioner's skills and preferences. In carrying out intubation, there is a need for an initial assessment of the airway, where there are several factors that influence the level of difficulty. Apart from that, there are also techniques to ensure that the patient is patient. His breathing was going well during intubation or ventilation. However, when carrying out techniques for intubation or ventilation, you need to pay attention to contraindications and future complications. After the surgical process, extubation strategies for difficult airways are carried out, this depends on the patient's condition and the anesthesiologist's abilities.